The putative sensor histidine kinase CKI1 is involved in female gametophyte development in Arabidopsis - Hejátko, J; Pernisová, M; Eneva, T; Palme, K; Brzobohatý, B (Molecular genetics and genomics, 2003)
Embryo sac formation is a fundamental step in sexual reproduction in plants. However, the key players involved in the development of the female gametophyte remain elusive. We present data indicating that a two-component sensor histidine kinase, CKI1, originally implicated in cytokinin perception, is required for completion of megagametogenesis in Arabidopsis. We isolated a loss-of-function mutation in CKI1 resulting from an insertion of the En-1 transposon into the CKI1 coding sequence. Genetic analysis revealed that the mutant allele, cki1-i, could not be transmitted through the female germ line. Confocal laser scanning microscopy identified a block in megagametogenesis, characterized by the abortion of the central vacuole in mutant embryo sacs, and degradation of the developing female gametophyte after completion of all mitotic divisions. The recovery of two independent stable alleles and one revertant wild-type allele resulting from En-1 excision confirmed unambiguously the causal link between the cki1-i mutation and the abnormal phenotype. In situ localization of CKI1 mRNA and histochemical analysis of stable transformants harboring the uidA gene under the control of CKI1 promoter revealed that expression of CKI1 starts at the very beginning of female gametophyte development, and continues until fertilization. This suggests that the developing embryo sac may remain sensitive to signals recognized by CKI1 throughout megagametogenesis. Furthermore, expression of the paternally transmitted CKI1 was detected early after fertilization. The results indicate a role for a two-component signaling system during female gametophyte development, and provide the first evidence that gametophytic expression of a sensor-like molecule is essential for specific processes during megagametogenesis.
Keywords: Molecular Sequence Data; proteinkinasy; semena rostlinná; sekvence nukleotidů; Base Sequence; sekvence aminokyselin; Arabidopsis Proteins; Seeds; molekulární sekvence - údaje; Protein Kinases; transpozibilní elementy DNA; Amino Acid Sequence; Arabidopsis; proteiny huseníčku; DNA Transposable Elements